Produtividade total de fatores no Brasil: impacto de investimentos em infraestrutura, efeitos do IDE e comparação internacional - Penha, Valéria de Luca (2015)
This paper examines the effects of infrastructure investments and Foreign Direct Investment (FDI) on Total Factor Productivity (TFP) based on international comparison. We use panel data for 50 countries, classified into three different categories - BRIC, fast growing countries and developed countries - from 1990 to 2010. We estimate impacts on Total Factor Productivity (TFP) by two steps. First, we investigate the role of infrastructure investments on TFP growth. Second, we extend the previous studies to examine whether Foreign Direct Investment (FDI) affect the development of TFP. The result indicates that the relationship among the data analyzed is significant, although improvements in infrastructure investments may enhance countries productivity more than an increase in FDI inflows does